CURRENT ACTIVITY IN THE THERMAIKOS GULF CONTINENTAL MARGIN , IN RELAÏJON TO MODERN SEDIMENTATION PROCESSES - Poulos, S. E.; Drakopoulos, P. G. (Bulletin of the Geological Society of Greece, 2018)
The area under investigation represents the NW continental margin of the Aegean Sea i.e. the Thermaikos Gulf and the associated NW Sporades Basin. Surficial seabed sediments are of terrigenous origin whilst in terms of grain size, offshore sediments maybe distinguished into silty sediments that cover the northern and western part of the Gulf; clayey that cover the floor of the Sporades basin and relict sands that cover mainly the central and eastern part of the self. Current meter measurements from different water depths were obtained from 10 stations on the shelf, shelf/break, within canyons and in the Sporades Basin. Surface currents over the period of the investigation are dominated by inertial currents generated by wind events. Inertial period currents also dominate the near-bed currents on the continental shelf and in Sporades Basin. On the canyon slope, however, tidal currents are the dominant ones; these relate to the amplification of the internal tide, within the submarine canyon. Measured near-bed currents are below the threshold for sediment movement in the case of flat seabeds, although they are capable to inhibit deposition of the settling clayey particles. This contributes also to a further offshore dispersal of riverine sediments. Moreover, increased bed roughness due to benthic activity can cause resuspension for lower current speeds.